Glucose Oxidase Induces Mobilization of Long-Term Repopulating Hematopoietic Cells in Mice. (23rd June 2021) - So, Han-Sol; Kim, Min-Guk; Lee, Jeong-Chae; Kook, Sung-Ho
Abstract: Hematopoietic stem progenitor cells (HSPCs) mobilized to peripheral blood, rather than those remaining in the bone marrow (BM), are commonly used as stem cell source in the clinic. As reactive oxygen species (ROS) are suggested as mediator of HSPC mobilization, we examined the impacts of glucose oxidase (GO) on peripheral mobilization of BM HSPCs and the associated mechanisms. Intravenous injection of GO induced HSPC mobilization even by single treatment, and the GO-mobilized cells maintained their long-term reconstituting and differentiating potentials in conditioned recipients. GO-injected mice lived a normal life without adverse effects such as stem cell senescence, hematopoietic disorders, and blood parameter alteration. The mobilization effect of GO was even evident in animal models showing poor mobilization, such as old, 5-fluorouracil-treated, or alendronate-treated mice. Importantly, combined injection of GO with granulocyte colony-stimulating factor (G-CSF) and/or AMD3100 enhanced more greatly HSPC mobilization than did G-CSF, AMD3100, or both. The GO-stimulated HSPC mobilization was almost completely attenuated by N -acetyl-L-cysteine treatment. Collectively, our results not only highlight the potential role of GO in HSPC mobilization via ROS signaling, but also provide a GO-based new strategy to improve HSPC mobilization in poorly mobilizing allogeneic or autologous donors via combination with G-CSF and/or AMD3100. : Single injection of glucose oxidase (GO) induces peripheral mobilization of hematopoietic stem progenitor cells (HSPCs) that maintain colony forming, repopulating, and multilineage differentiating potentials without hematopoietic disorders. Single GO injection not only mobilizes HPSCs even in the mice exhibiting poor HSPC mobilization, but also enhances synergistically mobilizer-induced HSPC mobilization. Collectively this study provides an evidence that combined treatment of GO with commonly used mobilizers augments therapeutic efficacy in HSPC transplantation without adverse events.